Comprehensive evaluation and spatial-temporal differences analysis of China’s inter-provincial doing business environment based on Entropy-CoCoSo method - Zhu, Yanmin; Zeng, Shouzhen; Lin, Zhisen; Ullah, Kifayat (Frontiers in Environmental Science, 2023)
The Doing Business environment affects the operation of enterprises in the region and exerts an important impact on economic development, taxation, and employment. According to the characteristics of large differences in the level of economic development between provinces in China, this study builds a set of scientific and reasonable evaluation index systems of inter-provincial Doing Business environment, including 5 first-level indicators and 11 second-level indicators. Moreover, this study constructs a comprehensive evaluation model based on the Entropy-CoCoSo framework and explores its application in China’s inter-provincial Doing Business environment evaluation. Based on China’s provincial panel data from 2007 to 2020, the research found that the Doing Business environment of each province has generally improved in recent years, but the inter-provincial differences are more prominent. The western provinces have obvious late-mover advantages. Finally, we put forward several targeted suggestions, providing a powerful reference for optimizing China’s Doing Business environment and promoting high-quality economic development.